Psychological Safety of Social Individuals in The Reality of The COVID-19 Pandemic - Ewa CHOMAĆ-PIERZECKA; Beata Maria NOWAK; Joanna ROGOZIŃSKA-MITRUT (Communications of International Proceedings, 2022)
Security is recognised as a fundamental determinant of effective functioning. Relating to social units, it is a fundamental value, associated with stability of living conditions. Anxiety or uncertainty (disturbed psychological safety) significantly reduces the quality of functioning. Uncertainty about the future has a limiting effect on development, lowers motivation and inhibits ambition. A natural attribute of the secure functioning of social units is to reduce their degree of uncertainty, thus increasing their level of security. The most difficult dimension of the risk of undermining the psychological security of individuals is that of force majeure. The authors of this paper draw attention to the problem of psychological safety of social units in the reality of the COVID-19 pandemic. They analyse the scope and strength of the impact of the pandemic on the functioning of individuals, touching simultaneously on the thread of the role of state institutions in reducing the degree of uncertainty of the risk of adverse events. The article is based on a review and critical appraisal of the available literature and studies with inference, as well as on the results of our own survey-like research.
Keywords: psychological safety; functional stability; individual safety; COVID-19.